PENGARUH NILAI TAMBAH EKSPOR DALAM PEMANFAATAN PENGOLAHAN KAYU JATI SEBAGAI PRODUK FURNITUR The Influence Of Export Added Value In The Use Of Teak Wood Processing As A Furniture Product - Alifah Nisrina Salsabila; Fazila Harnisa Putri; Irmaida Zahra Nariswari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The teak wood processing industry in Indonesia has developed into an important economic sector, especially in the manufacture of high quality furniture. The strength, durability and beauty of the fiber make teak wood very popular on the international market. The aim of this research is to study how the added value generated from the export of furniture made from teak wood impacts the country's economy. The teak wood processing industry has the potential to increase the competitiveness of Indonesian export products in the global market by optimally utilizing local natural resources. Research shows that optimizing export added value requires a comprehensive strategy involving increasing technological capacity, developing human resources, simplifying regulations, and strengthening branding in the global market. This has important consequences for the development policy of the wooden furniture industry